Marque and Reprisal : The Spheres of Public and Private War - Moss, Kenneth B. (Book collections on Project MUSE., 2019)
"Letters of marque" might suggest privateers of the Elizabethan era or the American Revolution. But such conventions are duly covered in the US Constitution, and the private military instruments they sanction are very much at work today in the form of mercenaries and military contractors. A history of such practices up to the present day, Marque and Reprisal by Kenneth B. Moss offers unique insight into the role of private actors in military conflicts and the reason they are increasingly deployed in our day. Along with an overview of mercenaries and privateers, Marque and Reprisal provides a comprehensive history of the "marque and reprisal" clause in the US Constitution, reminding us that it is not as arcane as it seems and arguing that it is not a license for all forms of undeclared war. Within this historical context Moss explains why governments and states have sought control over warfare and actors--and why private actors have reappeared in force in recent conflicts. He also looks ahead to the likelihood that cyberwar will become an important venue for "private warfare." Moss wonders if international law will be up to the challenges of private military actors in the digital realm. Is international law, in fact, equipped to meet the challenges increasingly presented in our day by such extramilitary activity? A government makes no more serious decision than whether to resort to military force and war; and when doing so, Moss suggests, it should ensure that such actions are accountable, not on the sly, and not decided in the marketplace. Marque and Reprisal should inform future deliberations and decisions on that count."--